Nonlinear optical and microscopic analysis of Cu2+ doped zinc thiourea chloride (ZTC) monocrystal. (1st February 2018) - Ramteke, S.P.; Anis, Mohd; Pandian, M.S.; Kalainathan, S.; Baig, M.I.; Ramasamy, P.; Muley, G.G.
Graphical abstract: Highlights: Reporting growth of 03 × 2.4 × 0.4 cm 3 bulk crystal of Cu 2+ ion doped ZTC (Cu-ZTC). SHG efficiency of Cu-ZTC crystal is 2.81 (ZTC) and 5.41 (KDP). Cu-ZTC crystal exhibit positive nonlinear refraction and reverse saturable absorption. The order of n2, β and χ 3 is 10 −7  cm 2 /W, 10 −1  cm/W and 10 −11 esu respectively. Nd:YAG laser induced surface damage threshold of Cu-ZTC crystal is 706.2 MW/cm 2 . Abstract: Organometallic crystals offer considerable nonlinear response therefore, present article focuses on bulk growth and investigation of Cu 2+ ion doped zinc thiourea chloride (ZTC) crystal to explore its technological impetus for laser assisted nonlinear optical (NLO) device applications. The Cu 2+ ion doped ZTC bulk single crystal of dimension 03 × 2.4 × 0.4 cm 3 has been grown from pH controlled aqueous solution by employing slow solvent evaporation technique. The structural analysis has been performed by means of single crystal X-ray diffraction technique. The doping of Cu 2+ ion in ZTC crystal matrix has been confirmed by means of energy dispersive spectroscopic (EDS) technique. The origin of nonlinear optical properties in Cu 2+ ion doped ZTC crystal has been studied by employing the Kurtz-Perry test and Z-scan analysis. The remarkable enhancement in second harmonic generation (SHG) efficiency of Cu 2+ ion doped ZTC crystal with reference to ZTC crystal has been determined. The He-Ne laser assisted Z-scan analysis has been performed to determine the third order nonlinear optical (TONLO) nature of grown crystal. The TONLO parameters such as susceptibility, absorption coefficient, refractive index and figure of merit of Cu-ZTC crystal have been evaluated using the Z-scan transmittance data. The laser damage threshold of grown crystal to high intensity of Nd:YAG laser is found to be 706.2 MW/cm 2 . The hardness number, work hardening index, yield strength and elastic stiffness coefficient of grown crystal has been investigated under microhardness study. The etching study has been carried out to determine the growth likelihood, nature of etch pits and surface quality of grown crystal.